Definition and categorization of rural and assessment of realized access to care. (7th March 2022) - Zahnd, Whitney E.; Del Vecchio, Natalie; Askelson, Natoshia; Eberth, Jan M.; Vanderpool, Robin C.; Overholser, Linda; Madhivanan, Purnima; Hirschey, Rachel; Edward, Jean
Abstract: Objective: To examine how three measures of realized access to care vary by definitions and categorizations of "rural". Data sources: Health Information National Trends Survey (HINTS) data, a nationally representative survey assessing knowledge of health‐related information, were used. Participants were categorized by county‐based Urban Influence Codes (UICs), Rural–Urban Continuum Codes (RUCCs), and census tract‐based Rural–Urban Commuting Area (RUCAs). Study design: Three approaches were used across categories of UICs, RUCCs, and RUCAs: (1) non‐metropolitan/metropolitan, (2) three‐group categorization based upon population size, and (3) three‐group categorization based on adjacency to metropolitan areas. Wald Chi‐square tests evaluated differences in sociodemographic variables and three measures of realized access across three of Penchansky's "A's of access" and approaches. The three outcome measures included: having a regular provider (realized availability), self‐reported "excellent" quality of care (realized acceptability), and self‐report of the provider "always" spending enough time with you (provider attentiveness–realized accommodation). The average marginal effects corresponding to each outcome were calculated. Data collection/extraction methods: N/A Principal findings: All approaches indicated comparable variation in sociodemographics. In all approaches, RUCA‐based categorizations showed differences in having a regular provider (e.g., 68.9% of non‐metropolitan and 64.4% of metropolitan participants had a regular provider). This association was attenuated in multivariable analyses. No rural–urban differences in quality of care were seen in unadjusted or adjusted analyses regardless of approach. After adjustment for covariates, rural respondents reported greater provider attentiveness in some categorizations of rural compared with urban (e.g., non‐metropolitan respondents reported 6.03 percentage point increase in probability of having an attentive provider [CI = 0.76–11.31%] compared with metropolitan). Conclusions: Our findings underscore the importance of considering multiple definitions of rural to understand access disparities and suggest that continued research is needed to examine the interplay between potential and realized access. These findings have implications for federal funding, resource allocation, and identifying health disparities.